OsAAP15, an amino acid transporter in response to nitrogen concentration, mediates panicle branching and grain yield in rice. (May 2023) - Yang, Xiuyan; Yang, Guo; Wei, Xilin; Huang, Weiting; Fang, Zhongming
Abstract: N is essential for plant architecture, particularly tillering. However, whether and how N mediates panicle branching and influences rice grain yield remains unclear. In order to identify genes and pathways associated with N-regulated panicle branching, we treated rice with different concentrations of N to determine the key genes by transcriptomic analysis and function verification. We measured panicle growth in response to N, and found that panicle branching benefits from 2 mM exogenous N, and 2–5 mM N is essential for vascular bundle, phloem, and xylem development in these branches. Interestingly, total N concentrations increased continuously with N 0–2 mM and decreased continuously with N 5–15 mM, whereas the concentrations of amino acids Tyr and Val increased continuously with N 0–15 mM in the panicle. Furthermore, N metabolism, phytohormone signal transduction, stress response, and photosynthesis pathways play important roles in response to nitrogen of regulating panicle branching. Altered expression of key N-response amino acid transporter gene OsAAP15 positively regulated panicle branching at low N concentrations, however, OsAAP15 negatively influenced it at high N concentrations. Overexpression of OsAAP15 in the field significantly increased primary and secondary branches, filled grain number, and grain yield by regulating the concentrations of amino acids Tyr and Val in the panicle. Taken together, OsAAP15, an amino acid transporter in response to nitrogen concentration, could mediate panicle branching and grain yield, and it may have applications in rice breeding to improve grain yield under extreme N concentrations. Highlights: Panicle branching benefits from 2 mM exogenous N, and 2–5 mM N is essential for vascular bundle, phloem, and xylem development in these branches. OsAAP15 positively regulated panicle branching at low N concentrations, however, OsAAP15 negatively influenced it at high N concentrations. Overexpression of OsAAP15 in the field significantly increased primary and secondary branches and grain yield by regulating of Tyr and Val.